Congruências modulares : construindo um conceito e as suas aplicações no ensino médio - Barbosa Junior, José Hélio (2013)
The purpose of this dissertation is to present to the students of basic education a powerful tool in the resolution of Arithmetic such as Modular Congruence. We initiate our study by approaching the main basics concepts of Number Theory: Divisibility, Eucledian Division, Greatest Common Divisor, Remainder modular arytmetics, culminating with Modular Congruence and its applications: Chinese Remainder Theorem and Intergers.